Sexualidade feminina em privação de liberdade: construindo relações sociais mais autênticas - Bassi, Silvana (2011)
This study reflects the practice of female sexuality in custody - as unique expression of the subject - and its interface with the context in which it is inserted. The importance of addressing this theme refers to the shortage of research with female adolescents who abide by social hospitalization in CASA Foundation / SP and to propose actions more attuned to the urgencies that are present. Sexuality - stigmatized and marred by prejudices and taboos - should be addressed to break paradigms, as advocated in legislation and policies aimed at children an adolescents. The proposal to discuss sexuality and spontaneously from the demands of teenagers led to the creation of a methodology of group dynamics, interactive and participatory, through which adolescents feel increasingly free to express their feelings their doubts and expectations. The research-in-action-of-intervention-training - used as a methodology - has broadened the perspectives of development of the growth process of the group. To the extent that the emerging content subsidized further discussion and turned into new buildings, the participants were involved in the dynamics and on track to establish more authentic